The relationship between executive functions and academic self-efficacy with ‎addiction to online games - masoud soltani nazarloo; mohammadagha delavarpour (مجله علوم روانشناختی)
Background: Nowadays, playing online games has become an integral part of the entertainment of male teenagers, so much so that for some of them, it is impossible to separate their lives from these types of games, and addiction to these games leads to these games. Studies have shown that some cognitive abilities such as appropriate executive functions and self-efficacy beliefs can be a deterrent and shock absorber of behavioral addictions similar to addiction to online games. Aims: This study aimed to investigate the relationship between executive functions and academic self-efficacy with online game addiction. Methods: The method of the present study was descriptive and correlational. The statistical population of this study consisted of all high school adolescents in Tehran in the academic year 2023-2024. The sample consisted of 250 high school students in Tehran who were selected by multi-stage cluster sampling. Data were collected using the Internet Gaming Disorder Questionnaire (Pontes et al, 2014), the Cognitive Abilities Questionnaire (Nejati, 2013), and the Academic Self-Efficacy Questionnaire (Morgan-Jinks et al., 2004). The collected data were analyzed using SPSS.27 software using Pearson correlation coefficient and multivariate regression. Results: The results of the Pearson correlation coefficient showed that there is a negative and significant relationship between academic self-efficacy and executive functions with online game addiction (P< 0.05). The results of multiple regression showed that 20% of the variance of online game addiction is explained by executive functions and academic self-efficacy. Conclusion: Therefore, executive functions and academic self-efficacy have many practical implications in the fields of research, etiology, and treatment of addiction to online games.